Analysis of the Influence of Brand Equity Elements on Consumers Purchase Intention of Packaged Tea Products - Desman Serius Nazara; Nugroho Djati Satmoko; Bambang Surahman; Sutrisno; Uli Wildan Nuryanto (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The goal of this study was to examine the relationship between brand awareness, brand association, perceived quality, and brand loyalty and consumer preference, as well as the relationship between brand awareness, brand association, perceived quality, and brand loyalty and purchase intention. Additionally, it examined the relationship between consumer preference and interest in purchasing as an intervention variable. The research was conducted purposefully from November to December 2022. Data sources were obtained through online survey results (primary data) and through literature (secondary data). Sampling using the incidental sampling method based on the Lemes how formula with an unknown population size produces a minimum of 100 samples. Data collection used a questionnaire with a Likert scale of 1-4. Descriptive analysis and SEM-PLS, which are utilized to analyze the data, are processed using Smart PLS 3.0 software. The findings demonstrated that brand loyalty and brand awareness variables had a direct impact on consumer preferences, however brand association variables and quality judgments did not. While brand awareness, brand associations, and brand loyalty do not directly affect purchase intention, perceived quality characteristics did have an impact on customer buying interest. The intention to purchase does not indirectly depend on perceived quality.